KEBUTUHAN AIR BERSIH BERBASIS PIPA PERUSAHAAN DAERAH AIR MINUM (PDAM) DI KECAMATAN TEBET - Achmad Sofyan; Khoe Susanto Kusumahadi; Sri Suci Utami Atmoko; Yeremiah Rubin Tjamin; Tatang Mitra Setia (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2022)
The fulfillment of clean water needs is one indicator of the level of quality of human life in an area, where clean water pipelines play an important role in supporting the fulfillment of the demand for clean water by the community. The population density of South Jakarta is 15,900 people per km2 with the highest population density is in Tebet District, namely 23,419 people per km2. As much as 51 percent of the population in Tebet uses groundwater as a source of clean water and the rest uses PAM water. The purpose of this study is to calculate the amount of clean water needs in the present condition and predict the water needs for the future conditions needed by residents in Tebet. By using the Stella 9.0.1 software, with the input of data on the number of villagers and the population growth rate, the population of Tebet District each year with a population growth graph can be determined to increase. It's different with projections that intervene with many factors, but show a decrease in water production and increase for domestic consumption, with projected weather variables not experiencing changes in water crises. In general, the trend of the level of water demand in 2019 and 2028 shows a decrease in water demand for irrigation, while the level of water demand for households, cities and industries (RKI) has increased.